In vitro antioxidant activity and in vivo photoprotective effect of Theobroma grandiflorum butter emulgels on skin of mice exposed to UVB irradiation - Aparicio-Álvarez, Chabely M.; Espinoza-Salazar, Catherine E.; Del Carpio-Jiménez, Carla (Frontiers in Sustainability, 2023)
Copoazú seed butter [Theobroma grandiflorum (Wild ex Spreng) K. Schum] is a rich source of fatty acids and polyphenols, active substances with high antioxidant and moisturizing activities and with potential applications in the cosmetic industry. Some studies have demonstrated that sun-induced skin damage is mediated partially by oxidative pathways, in fact, there is evidence for the photoprotective role of antioxidants. We examined the antioxidant activity and the effect of copoazú butter emulgels against UV-induced epidermal damage in mice to verify its use for topical photoprotective products. Topical treatment of mice with copoazú butter emulgels prior to each UV radiation exposure significantly reduced the severity of the damage. The in vitro determination of the sun protection factor (SPF) showed a value within the established range to be considered as a photoprotector, these results were corroborated by the in vivo results, since the mice irradiated with UV light and treated with copoazú emulgels showed less damage and was comparable with the standard photoprotector. The results showed that copoazú seed butter is an promising compound for photoprotective formulations.